تأثير الثقافة القطرية في تحقيق الأداء المؤسسي، دراسة تحليلية: THE IMPACT OF QATARI CULTURE ON INSTITUTIONAL PERFORMANCE REALIZATION: AN ANALYTICAL STUDY - Mohd A Al-Ansari, Faisal; Che Abdullah , Ahmad Sufian; Mohd Balwi , Mohd Abd Wahab Fatoni (Online Journal of Islamic Management and Finance (OJIMF), 2025)
Culture is a major component of societies and a key to understanding their ideas, behavior, and goals. Given that the Qatari citizen constitutes the most prominent component of government institutions in the State of Qatar, this issue must be given sufficient attention to understand its circumstances and analyze its diverse impact on institutional performance. The research problem is about the impact of Qatari culture on the institutional performance realization in the State of Qatar’s public institutions. Qatari culture is considered a significant contributor to realizing institutional performance in Qatar, although there are challenges that reduce the impact of Qatari culture on institutional performance realization. The research adopted the descriptive-analytical methodology as it is the best for achieving the research objectives, which are defining the concept of Qatari culture and institutional performance and determining the extent to which Qatari culture influences institutional performance. The research found that Qatari culture emphasizes cooperation, teamwork spirit, and strengthens belonging and commitment, which contributes to a team spirit and cooperation within the institution, increases job commitment, quality of production, and achievement of goals. In addition, there are challenges reducing the impact of Qatari cultural values on institutional performance. Addressing these challenges requires joint efforts from management, employees, and all members of the institution to ensure the successful application of Qatari culture and achieve the efficiency of the institutional performance. The researcher recommends the Islamic values and principles constituting the Qatari culture should be ensured and activated in institutions to ensure institutional performance and consolidate the Qatari culture.